2017
DOI: 10.1097/bpo.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Magnetically Controlled Growing Rods for Early Onset Scoliosis

Abstract: Level IV-retrospective nonrandomized objective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 28 publications
3
30
1
2
Order By: Relevance
“…It was a backtracking of the rod with, both times, complete loss of the gained length. To the best of our knowledge, failure of the system with backtracking has been reported twice before in the literature: one case by Ridderbusch et al [27] and six cases by Choi et al [26].…”
Section: (B)mentioning
confidence: 88%
“…It was a backtracking of the rod with, both times, complete loss of the gained length. To the best of our knowledge, failure of the system with backtracking has been reported twice before in the literature: one case by Ridderbusch et al [27] and six cases by Choi et al [26].…”
Section: (B)mentioning
confidence: 88%
“…The random disturbance or rather distribution of the measurements nicely reflects their poor reliability. This finding has significant clinical impact as PJK is a common complication of growing rod treatment and accurate assessment of the PJA is necessary for diagnosis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively modest amount of T1-T12 growth was achieved through lengthening surgeries - a mean of 2 cm over a mean of 6 growing rod lengthening surgeries and 8 VEPTR lengthening surgeries. Other studies have reported 1.65–2.1cm T1-T12 growth using growing rods 15,22 , 1.4–3.4 cm growth using magnetically controlled rods 16,18,19 , and 1.8–3.4 cm T1-T12 growth using rib-based constructs. 17,20,21 On the other hand, substantial increase in spinal length was obtained over the entire course of treatment (Table 2).…”
Section: Discussionmentioning
confidence: 94%